Serial theft from a criminal law perspective: A juridical analysis and a humanistic legal approach (study of decision No. 140/Pid.B/2024/PN.Kbu) - Osa Milda; M. Ruhly Kesuma Dinata (Journal of Law Science, 2026)
The escalation of aggravated theft as a conventional crime is increasingly disturbing the public, thus demanding stricter law enforcement. The urgency of this research is motivated by the complexity of judicial practices in applying aggravating elements which often trigger legal debate and legal uncertainty. This study examines in depth the Decision of the Kotabumi District Court Number 140/Pid.B/2024/PN.Kbu regarding the crime of aggravated theft as regulated in Article 363 paragraph (1) 4th and 5th of the Criminal Code. Using a juridical-normative method, this research is based on primary data in the form of judge's decisions and secondary data including statutory regulations and related legal literature. The study findings indicate that although the "aggravating" element has been legally fulfilled in this case, there is still a disparity in interpretation among law enforcement, particularly in distinguishing the roles of the main perpetrator and the accomplice. In addition, it was identified that economic pressures, a permissive social environment, and group ties have contributed significantly to the occurrence of this collective crime. Therefore, this study recommends the need for reform of criminal norms and the implementation of community-based prevention strategies as a more integrative solution in tackling crime.